Three-component synthesis of C2F5-substituted pyrazoles from C2F5CH2NH2·HCl, NaNO2 and electron-deficient alkynes - Mykhailiuk, Pavel K. (Beilstein Journal of Organic Chemistry, 2015)
A one-pot reaction between C2F5CH2NH2·HCl, NaNO2 and electron-deficient alkynes gives C2F5-substituted pyrazoles in excellent yields. The transformation smoothly proceeds in dichloromethane/water, tolerates the presence of air, and requires no purification of products by column chromatography. Mechanistically, C2F5CH2NH2·HCl and NaNO2 react first in water to generate C2F5CHN2, that participates in a [3 + 2] cycloaddition with electron-deficient alkynes in dichloromethane.
Keywords: cycloaddition; fluorine; pentafluoroethyl group; pentafluoroethyldiazomethane; pyrazole

Organofluorine Compounds – Chemistry and Application - Hiyama, T.; Yamamoto, T. (Springer, 2000)

Fluorine in Medicinal Chemistry and Chemical Biology - Ojima, I. (Blackwell Publishing, 2009)

Fluorine in Pharmaceutical and Medicinal Chemistry: From Biophysical Aspects to Clinical Applications - Gouverneur, V.; Müller, K. (Imperial College Press, 2012)

(untitled) - O'Hagan, D. (J. Fluorine Chem., 2010)

(untitled) - Müller, K.; Faeh, C.; Diederich, F. (Science, 2007)

(untitled) - Purser, S.; Moore, P. R.; Swallow, S.; Gouverneur, V. (Chem. Soc. Rev., 2008)

(untitled) - Hagmann, W. K. (J. Med. Chem., 2008)

(untitled) - Böhm, H.-J.; Banner, D.; Bendels, S.; Kansy, M.; Kuhn, B.; Müller, K.; Obst-Sander, U.; Stahl, M. (ChemBioChem, 2004)

(untitled) - Isanbor, C.; O'Hagan, D. (J. Fluorine Chem., 2006)

(untitled) - Bégué, J.-P.; Bonnet-Delpon, D. (J. Fluorine Chem., 2006)

(untitled) - Kirk, K. L. (J. Fluorine Chem., 2006)

(untitled) - Sun, A.; Yoon, J.-J.; Yin, Y.; Prussia, A.; Yang, Y.; Min, J.; Plemper, R. K.; Snyder, J. P. (J. Med. Chem., 2008)

(untitled) - Yonetoku, Y.; Kubota, H.; Okamoto, Y.; Toyoshima, A.; Funatsu, M.; Ishikawa, J.; Takeuchi, M.; Ohta, M.; Tsukamoto, S. (Bioorg. Med. Chem. Lett., 2006)

(untitled) - Yonetoku, Y.; Kubota, H.; Okamoto, Y.; Ishikawa, J.; Takeuchi, M.; Ohta, M.; Tsukamoto, S. (Bioorg. Med. Chem. Lett., 2006)

(untitled) - Yonetoku, Y.; Kubota, H.; Miyazaki, Y.; Okamoto, Y.; Funatsu, M.; Yoshimura-Ishikawa, N.; Ishikawa, J.; Yoshino, T.; Takeuchi, M.; Ohta, M. (Bioorg. Med. Chem., 2008)

(untitled) - Chowdhury, M. A.; Abdellatif, K. R. A.; Dong, Y.; Das, D.; Suresh, M. R.; Knaus, E. E. (J. Med. Chem., 2009)

(untitled) - Huang, K. H.; Veal, J. M.; Fadden, R. P.; Rice, J. W.; Eaves, J.; Strachan, J.-P.; Barabasz, A. F.; Foley, B. E.; Barta, T. E.; Ma, W.; Silinski, M. A.; Hu, M.; et al. (J. Med. Chem., 2009)

(untitled) - Maggio, B.; Raffa, D.; Raimondi, M. V.; Cascioferro, S.; Plescia, F.; Tolomeo, M.; Barbusca, E.; Cannizzo, G.; Mancuso, S.; Daidone, G. (Eur. J. Med. Chem., 2008)

(untitled) - Ward, S. E.; Harries, M.; Aldegheri, L.; Austin, N. E.; Ballantine, S.; Ballini, E.; Bradley, D. M.; Bax, B. D.; Clarke, B. P.; Harris, A. J.; Harrison, S. A.; Melarange, R. A.; et al. (J. Med. Chem., 2011)

(untitled) - Qi, J.; Zhang, F.; Mi, Y.; Fu, Y.; Xu, W.; Zhang, D.; Wu, Y.; Du, X.; Jia, Q.; Wang, K.; Zhang, H. (Eur. J. Med. Chem., 2011)

(untitled) - Djuric, S. W.; BaMaung, N. Y.; Basha, A.; Liu, H.; Luly, J. R.; Madar, D. J.; Sciotti, R. J.; Tu, N. P.; Wagenaar, F. L.; Wiedeman, P. E.; Zhou, X.; Ballaron, S.; et al. (J. Med. Chem., 2000)

(untitled) - Giornal, F.; Pazenok, S.; Rodefeld, L.; Lui, N.; Vors, J.-P.; Leroux, F. R. (J. Fluorine Chem., 2013)

(untitled) - Fustero, S.; Sánchez-Roselló, M.; Barrio, P.; Simón-Fuentes, A. (Chem. Rev., 2011)

(untitled) - Halcrow, M. A. (Dalton Trans., 2009)

(untitled) - Mukherjee, R. (Coord. Chem. Rev., 2000)

(untitled) - Jayaratna, N. B.; Gerus, I. I.; Mironets, R. V.; Mykhailiuk, P. K.; Yousufuddin, M.; Dias, H. V. R. (Inorg. Chem., 2013)

(untitled) - Gerus, I. I.; Mironetz, R. X.; Kondratov, I. S.; Bezdudny, A. V.; Dmytriv, Y. V.; Shishkin, O. V.; Starova, V. S.; Zaporozhets, O. A.; Tolmachev, A. A.; Mykhailiuk, P. K. (J. Org. Chem., 2012)

(untitled) - Wishart, D. S.; Knox, C.; Guo, A. C.; Cheng, D.; Shrivastaya, S.; Tzur, D.; Gautam, B.; Hassanali, M. (Nucleic Acids Res., 2008)
At least 45 FDA-approved drugs contain the trifluoromethyl group.

(untitled) - Ma, J.-A.; Cahard, D. (Chem. Rev., 2004)

(untitled) - Macé, Y.; Magnier, E. (Eur. J. Org. Chem., 2012)

(untitled) - Altomonte, S.; Zanda, M. (J. Fluorine Chem., 2012)

(untitled) - Andrzejewska, M.; Yépez-Mulia, L.; Cedillo-Rivera, R.; Tapia, A.; Vilpo, L.; Vilpo, J.; Kazimierczuk, Z. (Eur. J. Med. Chem., 2002)

(untitled) - Johansson, A.; Poliakov, A.; Åkerblom, E.; Wiklund, K.; Lindeberg, G.; Winiwarter, S.; Danielson, U. H.; Samuelsson, B.; Hallberg, A. (Bioorg. Med. Chem., 2003)

(untitled) - Jonat, W.; Bachelot, T.; Ruhstaller, T.; Kuss, I.; Reimann, U.; Robertson, J. F. R. (Ann. Oncol., 2013)

(untitled) - Croxtall, J. D.; McKeage, K. (Drugs, 2011)

(untitled) - Taka, N.; Koga, H.; Sato, H.; Ishizawa, T.; Takahashi, T.; Imagawa, J. (Bioorg. Med. Chem., 2000)

(untitled) - Pazenok, S.; Giornal, F.; Landelle, G.; Lui, N.; Vors, J.-P.; Leroux, F. R. (Eur. J. Org. Chem., 2013)

(untitled) - Desens, W.; Winterberg, M.; Büttner, S.; Michalik, D.; Saghyan, A. S.; Villinger, A.; Fischer, C.; Langer, P. (Tetrahedron, 2013)

(untitled) - Khlebnikova, T. S.; Piven, Yu. A.; Baranovskii, A. V.; Lakhvich, F. A. (Russ. J. Org. Chem., 2013)

(untitled) - Fustero, S.; Román, R.; Sanz-Cervera, J. F.; Simón-Fuentes, A.; Cuñat, A. C.; Villanova, S.; Murguía, M. (J. Org. Chem., 2008)

(untitled) - Man, S.; Nečas, M.; Bouillon, J.-P.; Portella, C.; Potáček, M. (Eur. J. Org. Chem., 2006)

(untitled) - Martins, M. A. P.; Pereira, C. M. P.; Zimmermann, N. E. K.; Cunico, W.; Moura, S.; Beck, P.; Zanatta, N.; Bonacorso, H. G. (J. Fluorine Chem., 2003)

(untitled) - Li, F.; Nie, J.; Sun, L.; Zheng, Y.; Ma, J.-A. (Angew. Chem., Int. Ed., 2013)

(untitled) - Slobodyanyuk, E. Y.; Artamonov, O. S.; Shishkin, O. V.; Mykhailiuk, P. K. (Eur. J. Org. Chem., 2014)

(untitled) - Mykhailiuk, P. K. (Chem. – Eur. J., 2014)

(untitled) - Husted, D. R.; Ahlbrecht, A. H. (J. Am. Chem. Soc., 1953)
C2F5CH2NH2·HCl can be prepared from pentafluoropropyonic acid according to this literature.

Diazo Chemistry I and II - Zollinger, H. (VCH, 1994)

(untitled) - Huisgen, R. (Angew. Chem., Int. Ed., 1963)

Synthetic Applications of 1,3-Dipolar Cycloaddition Chemistry toward Heterocycles and Natural Products - Maas, G. (Diazoalkanes, 2002)

(untitled) - Gilman, H.; Jones, R. G. (J. Am. Chem. Soc., 1943)

(untitled) - Lahm, G. P.; Selby, T. P.; Freudenberger, J. H.; Stevenson, T. M.; Myers, B. J.; Seburyamo, G.; Smith, B. K.; Flexner, L.; Clark, C. E.; Cordova, D. (Bioorg. Med. Chem. Lett., 2005)

(untitled) - Sun, A.; Chandrakumar, N.; Yoon, J.-J.; Plemper, R. K.; Snyder, J. P. (Bioorg. Med. Chem. Lett., 2007)